2020
DOI: 10.1371/journal.pone.0241447
|View full text |Cite
|
Sign up to set email alerts
|

Cerumen microbial community shifts between healthy and otitis affected dogs

Abstract: Otitis externa is a common multifactorial disease in dogs, characterized by broad and complex modifications of the ear microbiota. The goal of our study was to describe the ear cerumen microbiota of healthy dogs, within the same animal and between different animals, and to compare the cerumen microbiota of otitis affected dogs with that of healthy animals. The present study included 26 healthy dogs, 16 animals affected by bilateral otitis externa and 4 animals affected by monolateral otitis externa. For each a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
2
15
0
1
Order By: Relevance
“…This observation highlights that, at least for the detection of P. aeruginosa, bacterial culture appears to be a sensitive method. The presence of P. aeruginosa in canine otitis externa with/without otitis media has been reported in several studies [5,7,[10][11][12]14,15,26,[28][29][30][31][32][33]. A prevalence from 7.2% to 35.5% of P. aeruginosa was recorded in bacterial culture [5,7,26,28,30,31,33].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This observation highlights that, at least for the detection of P. aeruginosa, bacterial culture appears to be a sensitive method. The presence of P. aeruginosa in canine otitis externa with/without otitis media has been reported in several studies [5,7,[10][11][12]14,15,26,[28][29][30][31][32][33]. A prevalence from 7.2% to 35.5% of P. aeruginosa was recorded in bacterial culture [5,7,26,28,30,31,33].…”
Section: Discussionmentioning
confidence: 98%
“…This discrepancy could be explained by the presence of uncultured bacteria or the emergence of the fastest-growing bacteria. Recent studies using 16S amplicon profiling have shown that the bacterial population observed in canine otitis externa is more complex than expected based on the bacterial culture technique [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the features found in negative controls (Supplementary Table S1) were either absent or present in a negligible number of analyzed samples. Based on this evidence and the best practices for analyzing microbiomes [27][28][29], and in consideration of similar studies in the literature [36,37], we decided to filter out low abundance ASVs by removing all the features with a minimum frequency <150. Following taxonomic analysis, the analysis of the composition of microbiomes (ANCOM) implemented through the QIIME2 ANCOM plugin was carried out to evaluate the presence of statistical differences of population abundance between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates were cultured from the ear (6.1%), eye (4.4%), genitalia and rectum (both 3.1%) (Park et al, 2020). Microbiome studies in healthy dogs and those with otitis reported that Pseudomonadaceae were present in both groups, but the relative abundance differed with a higher abundance detected in dogs with otitis (Borriello et al, 2020). However, other studies have found very little evidence of Pseudomonas spp.…”
Section: Morbiditymentioning
confidence: 99%